Resin composition and cured product
By adding layered clay minerals to the resin composition, the problem of insufficient thermal conductivity and heat resistance of the existing resin encapsulation materials is solved, and a resin cured molded product with excellent properties such as high thermal conductivity, low thermal expansion and heat resistance is achieved.
Patent Information
- Application Number
- CN202380056676.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2023-08-03
- Publication Date
- 2025-03-11
AI Technical Summary
The existing resin encapsulation materials have shortcomings in improving thermal conductivity, heat resistance and thermal expansion, and increasing the content of inorganic filler materials will lead to increased viscosity and decreased moldability.
A resin composition containing a layered clay mineral is used, and specifically, a crystalline resin and a layered clay mineral are used as additives, and 1 to 20 parts by weight of the layered clay mineral is contained with respect to 100 parts by weight of the resin component.
It has achieved a cured molded product with excellent moldability, reliability and high thermal conductivity, low thermal expansion, heat resistance, moisture resistance and flame retardancy, and is suitable for semiconductor packaging, laminated plates and heat dissipation substrates and other applications.
Smart Images

Figure BDA0005258047550000041 
Figure BDA0005258047550000042 
Figure BDA0005258047550000051
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition useful as an insulating material for electrical and electronic materials such as semiconductor packages, laminates, and heat dissipation substrates having excellent reliability, and a cured product made of the resin composition. Background Art
[0002] In the past, as a packaging method for electrical and electronic components such as diodes, transistors, integrated circuits, semiconductor devices, etc., a packaging method using, for example, epoxy resin or silicone resin, or a hermetic packaging method using glass, metal, ceramic, etc. was adopted. However, in recent years, resin packaging using transfer molding has become the mainstream, which has improved reliability, enables mass production, and has cost advantages.
[0003] Among the resin compositions used for resin encapsulation by transfer molding, encapsulating materials composed of a resin composition containing an epoxy resin and a phenol resin as a curing agent as main components are generally used.
[0004] Epoxy resin compositions used for the purpose of protecting devices such as power devices are densely filled with inorganic fillers such as crystalline silica in order to cope with the large amount of heat released by the devices.
[0005] Power devices include single-chip devices that incorporate IC technology, and modular devices. It is desired to further improve the heat dissipation, heat resistance, and thermal expansion resistance of packaging materials.
[0006] In addition, printed circuit boards, packaging materials, and casting materials used in communication equipment are also actively researching high-speed communication technologies to increase signal transmission speeds as communication speeds and communication volumes increase. Electronic materials in such applications require materials that can reduce dielectric loss, and printed circuit board applications require curable resins that can be multilayered.
[0007] On the other hand, the electronic computing components that process such a large amount of data generate a lot of heat, and the heat accumulation causes the processing speed of the electronic computing components to decrease. Therefore, as a technology for appropriately cooling the printed circuit board using a heat sink, there are various known designs such as assembling heat-conducting components such as copper coins and copper inlays (Patent Document 1), or making the shape of the matching filler a special shape (Patent Document 2). However, such a method leads to an increase in weight or an increase in the size of the device, so it is not preferred.
[0008] In addition, as a method for improving thermal conductivity in a packaging material composition, a method for removing heat from electronic computing components by studying the types and amounts of various fillers is adopted. For example, attempts have been made to make it contain inorganic fillers such as crystalline silicon dioxide, silicon nitride, aluminum nitride, and spherical aluminum oxide powder with large thermal conductivity (Patent Documents 3 and 4). However, if the content of the inorganic filler is increased, the viscosity during molding increases and the fluidity decreases, which impairs the moldability. Therefore, the method of simply increasing the content of the inorganic filler is limited.
[0009] Based on the above background, the method of improving the thermal conductivity of the composition by the high thermal conductivity of the matrix resin itself has also been studied. For example, an epoxy resin with a liquid crystal of a rigid mesogenic group and an epoxy resin composition using the epoxy resin (patent documentation 5, 6) have been proposed. However, as the curing agent used in these epoxy resin compositions, an aromatic diamine compound is used, and the high filling rate of the inorganic filler is limited, and there are also problems in terms of electrical insulation. In addition, when using an aromatic diamine compound, although the liquid crystal of the cured product can be confirmed, the crystallinity of the cured product is low, and it is insufficient in terms of high thermal conductivity, low thermal expansion, low hygroscopicity, etc. Further, in order to present liquid crystal, it is necessary to apply a strong magnetic field to orient the molecules, and in order to be widely used in industry, there are also great restrictions on equipment. In addition, in the coordination system with the inorganic filler, the thermal conductivity of the inorganic filler is overwhelmingly greater than the thermal conductivity of the matrix resin, even if the thermal conductivity of the matrix resin itself is improved, the reality is that the contribution to improving the thermal conductivity as a composite material is not large, and the existing resin cannot obtain sufficient thermal conductivity improvement effect.
[0010] Layered clay minerals such as talc are generally used to improve fluidity or reduce the linear expansion coefficient. It has been proposed to combine layered clay minerals with inorganic fillers with high thermal conductivity, but the high thermal conductivity is caused by the contact between inorganic substances, and does not act on the matrix resin itself (Patent Document 7).
[0011] Patent document 8 discloses a tetrafunctional or higher vinyl resin having a biphenyl skeleton as a multifunctional vinyl resin having both high thermal conductivity and low dielectric loss tangent. However, the solvent solubility of the multifunctional vinyl resin and the polyhydroxy resin as its raw material is not recorded, nor is the influence of impurities such as residual polar groups on thermal conductivity mentioned.
[0012] Prior art literature
[0013] Patent Literature
[0014] Patent Document 1: Japanese Patent Application Publication No. 2009-170493
[0015] Patent Document 2: International Publication No. WO2013 / 100172
[0016] Patent Document 3: Japanese Patent Application Laid-Open No. 11-147936
[0017] Patent Document 4: Japanese Patent Application Publication No. 2002-309067
[0018] Patent Document 5: Japanese Patent Application Laid-Open No. 11-323162
[0019] Patent Document 6: Japanese Patent Application Laid-Open No. 9-118673
[0020] Patent Document 7: International Publication No. WO2013 / 100174
[0021] Patent Document 8: International Publication No. WO2021 / 200414 Summary of the invention
[0022] Therefore, an object of the present invention is to provide a resin composition and a cured product thereof which can solve the above-mentioned problems.
[0023] For example, the epoxy resin composition of the first embodiment described below provides a molded product having excellent moldability and reliability, high thermal conductivity, low thermal expansion, heat resistance, moisture resistance, and flame retardancy, and can provide a molded product in which crystallinity is observed in XRD.
[0024] In addition, for example, with respect to the vinyl resin composition of the second embodiment described later, a vinyl resin composition useful in packaging of electrical and electronic components, circuit board materials, etc. and a cured product thereof are provided, wherein the vinyl resin composition provides a cured product having excellent solvent solubility and moldability and excellent heat resistance, thermal decomposition stability, thermal conductivity, low dielectric constant, low dielectric loss tangent, and flame retardancy.
[0025] The present inventors have conducted intensive studies and have found that a resin composition containing a layered clay mineral is expected to solve the above-mentioned problems, and that a cured product thereof exhibits at least a thermal conductivity effect and, in some cases, effects such as a low dielectric constant and a low dielectric loss tangent.
[0026] That is, the gist of the present invention is as follows.
[0027] [1] A resin composition comprising at least a crystalline resin and an additive, wherein the additive is a layered clay mineral, and the layered clay mineral is contained in an amount of 1 to 20 parts by weight based on 100 parts by weight of the resin component.
[0028] The melting point of the crystalline resin is higher than 80° C. and lower than 200° C.
[0029] [2] The resin composition according to [1], wherein the additive is talc or mica.
[0030] [3] The resin composition according to [2], wherein the additive is talc.
[0031] [4] The resin composition according to [1], wherein the crystalline resin is an epoxy resin and / or a vinyl resin.
[0032] [5] The resin composition according to [4], wherein the crystalline resin is an epoxy resin having a melting point of greater than 80°C and less than 180°C and / or a vinyl resin having a melting point of 90 to 200°C.
[0033] [6] The resin composition according to any one of [1] to [5], characterized in that the crystalline resin is an epoxy resin, the resin composition contains a curing agent, and in the measurement of the cured product of the resin composition using X-ray diffraction (XRD), a diffraction peak is detected in a region where the diffraction angle 2θ is greater than 15° and less than 25°.
[0034] [7] The resin composition according to [6], wherein the epoxy resin is represented by the following general formula (1-1) or (1-2).
[0035]
[0036] (In formula (1-1), G represents a glycidyl group, A independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO- or a divalent hydrocarbon group having 1 to 6 carbon atoms, and n represents a number from 0 to 20)
[0037]
[0038] (In formula (1-2), Y independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO-, -COO-, -CONH-, -CH2- or -C(CH3)2-. B independently represents a benzonitrile structure or -(CH2) q -, p represents a number from 0 to 15, q represents a number from 3 to 10)
[0039] [8] A resin composition according to any one of [1] to [5], wherein the crystalline resin is a vinyl resin having a vinyl equivalent of 150 to 1000 g / eq, a hydroxyl equivalent of 5000 g / eq or more, and a total chlorine content of 2000 ppm or less.
[0040] [9] The resin composition according to [8], wherein the vinyl resin is represented by any one or more of the following general formulas (2-1) to (2-3).
[0041]
[0042] (In formula (2-1), R 1 ~R 6 Each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms)
[0043]
[0044] (In formula (2-2), A independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO- or a divalent hydrocarbon group having 1 to 6 carbon atoms, X independently represents a benzene ring, a naphthalene ring or a biphenyl ring, and n represents a number from 0 to 20)
[0045]
[0046] (In formula (2-3), Y independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO-, -COO-, -CONH-, -CH2- or -C(CH3)2-. B independently represents a benzonitrile structure or -(CH2) q -, p represents a number from 0 to 15, q represents a number from 3 to 10)
[0047]
[10] The resin composition according to any one of [1] to [5], characterized in that it contains 20 to 90 wt% of an inorganic filler other than the layered clay mineral.
[0048]
[11] The resin composition according to any one of [1] to [5], which is a resin composition that provides a cured product with high thermal conductivity.
[0049]
[12] The resin composition according to [6], which is a resin composition that provides a cured product having a crystallinity of 10% or more for high thermal conductivity.
[0050]
[13] A cured product obtained by curing the resin composition according to any one of [1] to [5].
[0051] The resin composition of the present invention provides, for example, a cured molded product having excellent moldability and reliability, high thermal conductivity, low water absorption, low thermal expansion, high heat resistance, and excellent flame retardancy. In addition, for example, a resin composition and a cured product thereof that are suitable for use in applications such as lamination, molding, casting, and bonding, and the cured product also has excellent heat resistance, thermal decomposition stability, thermal conductivity, low dielectric constant, low dielectric loss tangent, and flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 This is an XRD pattern of the cured product of the epoxy resin composition obtained in Example 1-1 in the first embodiment.
[0053] Figure 2 This is an XRD chart of the cured product of the epoxy resin composition obtained in Comparative Example 1-1 in the first embodiment.
[0054] Figure 3 This is a GPC chart of the vinyl resin A obtained in Synthesis Example 2-1 in the second embodiment.
[0055] Figure 4 This is a GPC chart of the vinyl resin B obtained in Synthesis Example 2-2 in the second embodiment.
[0056] Figure 5 This is a GPC chart of the vinyl resin C obtained in Synthesis Example 2-3 in the second embodiment.
[0057] Figure 6 This is an FD-MS spectrum of the vinyl resin C obtained in Synthesis Example 2-3 in the second embodiment. DETAILED DESCRIPTION
[0058] The present invention will be described in detail below. Specifically, as described below, a first embodiment and a second embodiment will be described by way of example.
[0059] The resin composition of the present invention is characterized in that it is a resin composition comprising at least a crystalline resin and an additive, wherein the additive is a layered clay mineral, and the layered clay mineral is contained in an amount of 1 to 20 parts by weight relative to 100 parts by weight of the resin component, and the melting point of the crystalline resin is greater than 80°C and less than 200°C.
[0060] The resin in the resin composition of the present invention uses a crystalline resin having crystallinity at room temperature. Here, the crystalline resin has the same meaning as that commonly used in the art, and is a resin having a crystalline structure. In addition, the crystalline resin refers to a resin showing a clear endothermic peak in differential scanning calorimetry analysis.
[0061] As crystalline resin, there is no restriction, can be suitably selected according to purpose, for example, can enumerate acrylic resin, styrene-acrylic resin, polyester resin, epoxy resin, vinyl resin etc..These resins can use 1 kind, also can use 2 kinds or more.In these crystalline resins, if consider the above-mentioned various characteristics as the purpose of the present invention, then from the viewpoint of formability, reliability, high thermal conductivity, low water absorption, heat resistance, low thermal expansion, heat resistance, moisture resistance, flame retardancy, preferred epoxy resin.In addition, from the aspect of solvent solubility, excellent formability, heat resistance, thermal decomposition stability, thermal conductivity, low dielectric constant, low dielectric loss tangent, excellent flame retardancy, preferred vinyl resin.
[0062] The crystalline resin of the present invention has a melting point. The melting point ranges from greater than 80°C to less than 200°C. Although it depends on the resin used, it is preferably above 90°C in order to improve thermal conductivity or for reliability and heat resistance. Here, the melting point refers to the endothermic peak temperature accompanying the melting of the crystal in differential scanning calorimetry. Resins with a melting point higher than 200°C tend to have strong crystallinity, reduced solvent solubility, and melt kneading properties, and cured products using resins with a melting point of less than 80°C tend not to have improved thermal conductivity.
[0063] The layered clay mineral as the additive used in the resin composition of the present invention is also referred to as a flat particle, specifically, comprising talc, kaolin, mica, montmorillonite, beidellite, hectorite, saponite, nontronite, montmorillonite and other montmorillonite minerals, vermiculite, bentonite, kanemite, kenyaite, makatite and other layered sodium silicates, Na-type tetrasilicon fluoride mica, Li-type tetrasilicon fluoride mica, Na-type fluorine-banded mica, Li-type fluorine-banded mica and other mica family clay minerals etc. They can be obtained by natural minerals, or chemical synthesis is possible. And then, the layered clay mineral can be a material formed by surface modification (surface treatment) such as ammonium salts. Especially from the viewpoint of good thermal conductivity, it is preferably a silicate compound comprising magnesium, more preferably talc, mica, and further preferably talc.
[0064] Relative to 100 parts by weight of the total amount of the resin component, 1 to 20 parts by weight of a layered clay mineral is included. Preferably, 5 to 15 parts by weight are included. If the amount of the layered clay mineral in the resin composition is too small, it is sometimes difficult to fully exert the above-mentioned thermal conductivity. On the other hand, when the content of the layered clay mineral is more than this range, sometimes the fluidity and heat resistance decrease. In addition, when containing inorganic fillers with high thermal conductivity such as alumina, if the amount of the layered clay mineral is large, sometimes the content of the inorganic filler with high thermal conductivity is insufficient, and the overall thermal conductivity decreases. Here, the resin component refers to a resin and its cured or modified components, etc. For example, in the first embodiment described later, the resin component refers to an epoxy resin, a curing agent, and a curing accelerator contained as needed. In addition, in the second embodiment described later, the resin component refers to a vinyl resin and a free radical polymerization initiator and a modifier contained as needed. The resin component can be appropriately changed for use according to the purpose.
[0065] The resin composition of the present invention is not limited as long as the object of the present invention is achieved and not impaired, except for using a crystalline resin having a melting point within the above-specified range and a layered clay mineral as an additive in an amount within the above-specified range.
[0066] In order to explain the specific embodiments of the present invention, the first embodiment using epoxy resin as the crystalline resin and the second embodiment using vinyl resin as the crystalline resin are exemplified below. As described above, epoxy resin and vinyl resin are preferred embodiments that satisfy several of the various properties that are the purpose of the present invention, and the scope of the present invention is not limited to these embodiments.
[0067] <First embodiment>
[0068] Hereinafter, a first embodiment of the present invention will be described in detail.
[0069] First, the first embodiment of the present invention relates to an epoxy resin composition using an epoxy resin as a crystalline resin. In the first embodiment, it is preferably an epoxy resin composition containing a curing agent together with the above-mentioned additive (layered clay mineral) and epoxy resin. The curing agent is described below. For the epoxy resin composition of the first embodiment, in the measurement (XRD) of its cured product using X-ray diffraction method, the epoxy resin composition in which a diffraction peak is observed in a specified area is a preferred embodiment, and more specifically, it is preferred that a diffraction peak is observed in a region where the diffraction angle 2θ is 15° or more and less than 25°. Usually, the spectrum when XRD measurement is performed on an epoxy resin cured product composed only of organic matter is broad, and no clear peak is detected. When crystallinity is shown, a sharp peak can be detected, and the detection range is in a region where 2θ is 15° or more and less than 25°. In addition, when an inorganic substance is contained in the epoxy resin composition, although the peak of the inorganic substance is detected, the peak position is different according to the crystal structure and can be distinguished from the peak of the organic substance. When the additive (layered clay mineral) is talc, a diffraction peak is observed in the region of 28° to 29° at 2θ. Here, a broad peak is also referred to as an amorphous peak, which is a peak having a width of 8° or more, and a sharp peak is also referred to as a crystalline peak, which is a peak having a width of within 5°, preferably within 3°. That is, the "diffraction peak is detected" in the first embodiment means that the sharp peak (crystalline peak) is preferably detected in a range of 2θ of 15° or more and less than 25°. It should be noted that the width of the peak refers to the width between the starting point of the rise and the end point of the fall that can be obtained by a conventional peak analysis method performed by a person skilled in the art, which is usually parallel to the baseline and between the rising start point and the falling end point of the peak.
[0070] As described above, the epoxy resin component of the epoxy resin composition of the first embodiment of the present invention has a melting point of more than 80° C. and less than 200° C. The preferred lower limit is 83° C. or more, and the more preferred lower limit is 90° C. or more. On the other hand, the preferred upper limit is 180° C. or less, and the more preferred upper limit is 150° C. or less.
[0071] The epoxy resin component of the epoxy resin composition of the first embodiment of the present invention can be any epoxy resin having two or more epoxy groups in the molecule. For example, there are diphenols such as bisphenol A, bisphenol F, 4,4'-dihydroxydiphenyl ether, hydroquinone, 4,4'-dihydroxybiphenyl, 3,3',5,5'-tetramethyl-4,4'-dihydroxydiphenylmethane, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfide, fluorene bisphenol, 2,2'-biphenol, resorcinol, catechol, tert-butylcatechol, tert-butylhydroquinone, allylated bisphenol A, allylated bisphenol F, allylated phenol novolac, or phenol novolac, bisphenol A novolac, o-cresol novolac, m-cresol novolac, Phenols having trivalent or higher valence such as p-cresol novolac, xylenol novolac, poly-p-hydroxystyrene, tris(4-hydroxyphenyl)methane, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, phloroglucinol, pyrogallol, tert-butylpyrogallol, allylated pyrogallol, polyallylated pyrogallol, 1,2,4-pyrogallol, 2,3,4-trihydroxybenzophenone, phenol aralkyl resin, naphthol aralkyl resin, dicyclopentadiene resin, or glycidyl ethers derived from raw material phenolic compounds such as halogenated bisphenols such as tetrabromobisphenol A, etc. These epoxy resins can be used in one or more kinds. In addition, epoxy resins having a mesogenic group can also be used in one or more kinds.
[0072] As the epoxy resin, preferably, 4,4'-dihydroxydiphenyl ether, hydroquinone, 4,4'-dihydroxybiphenyl derived glycidyl ether, a highly thermally conductive epoxy resin having a rigid structure such as a mesogenic skeleton, etc., is used, and the epoxy resin represented by the above general formula (1-1) or (1-2) is particularly preferred. Preferably, these highly thermally conductive epoxy resins contain more than 50wt% of the total epoxy resin component. More preferably, it is more than 70wt%. If the use ratio is smaller than this range, sometimes the effect of improving the heat resistance, thermal conductivity, etc. when the epoxy resin cured product is made is small.
[0073] In the above general formula (1-1), n is a repetition number (number average), which represents a number from 0 to 20. A mixture of components having different n values is preferred. In addition, G represents a glycidyl group, and A independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO-, or a divalent hydrocarbon group having 1 to 6 carbon atoms. From the viewpoint of thermal conductivity, A is preferably a single bond.
[0074] In the above general formula (1-2), p is the repetition number (number average), which represents a number from 0 to 15. It is preferably a mixture of components with different p values. In addition, Y independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO-, -COO-, -CONH-, -CH2- or -C(CH3)2-. From the perspective of high thermal conductivity, Y is preferably a single-bond biphenyl structure, -SO2-, -CO-, -COO-, -CONH-, and a biphenyl structure at the 4,4' position is particularly preferred. On the other hand, from the perspective of moldability and solvent solubility, Y is preferably an oxygen atom, a sulfur atom, -CH2-, -C(CH3)2-. In addition, B in formula (1-2) independently represents a benzonitrile structure or -(CH2) q -, q represents a number of 3 to 10. Preferably, B has both structures in at least one molecule.
[0075] The preparation method of the epoxy resin used in the epoxy resin composition of the first embodiment of the present invention is not particularly limited, and can be prepared by reacting the phenolic compound of the raw material with epichlorohydrin. The reaction can be carried out in the same manner as a conventional epoxidation reaction. The phenolic compound of the raw material can use a phenolic compound that matches the epoxy resin obtained as described above. In addition, the epoxy resin represented by the above formula (1-1) or (1-2) can be prepared as follows.
[0076] The epoxy resin represented by the formula (1-1) can be produced by reacting a polyhydroxy resin (raw material phenolic compound) represented by the following formula (1-3) with epichlorohydrin.
[0077]
[0078] Here, A and n in formula (1-3) are the same as those in the above formula (1-1).
[0079] The polyhydroxy resin (1-3) can be produced by reacting an aromatic crosslinking agent having a biphenyl structure represented by the formula (1-4) with a bifunctional phenol compound represented by the formula (1-5).
[0080]
[0081] Here, Z in the formula (1-4) represents a hydroxyl group, a halogen atom, or an alkoxy group having 1 to 6 carbon atoms.
[0082]
[0083] Here, A in formula (1-5) is the same as that in the above formula (1-1).
[0084] In the aromatic crosslinking agent represented by the above formula (1-4), Z represents a hydroxyl group, a halogen atom, or an alkoxy group having 1 to 6 carbon atoms. Specific examples of the aromatic crosslinking agent include 4,4'-bishydroxymethylbiphenyl, 4,4'-bischloromethylbiphenyl, 4,4'-bisbromomethylbiphenyl, 4,4'-bismethoxymethylbiphenyl, and 4,4'-bisethoxymethylbiphenyl. From the viewpoint of reactivity, 4,4'-bishydroxymethylbiphenyl or 4,4'-bischloromethylbiphenyl is preferred, and from the viewpoint of reducing ionic impurities, 4,4'-bishydroxymethylbiphenyl or 4,4'-bismethoxymethylbiphenyl is preferred.
[0085] In addition, as the bifunctional phenol compound of formula (1-5), specifically, 2,2'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxybenzophenone, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfide, dihydroxydiphenylmethanes, and 2,2-bis(4-hydroxyphenyl)propane are preferred. In particular, from the perspective of solvent solubility, 2,2'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, and dihydroxydiphenylmethanes are preferred. Dihydroxydiphenylmethanes may be a mixture of ortho, meta, and para, and the isomer ratio of 4,4'-dihydroxydiphenylmethane is preferably 40% or less. If there is a large amount of 4,4'-dihydroxydiphenylmethane, there is a concern that the crystallinity is strong and the solvent solubility is reduced.
[0086] The molar ratio when the aromatic crosslinking agent of formula (1-4) is reacted with the phenol compound of formula (1-5) is generally in the range of 0.2 to 0.7 moles of the aromatic crosslinking agent relative to 1 mole of the phenol compound, and more preferably in the range of 0.4 to 0.7 moles. The reaction can be carried out without a catalyst or in the presence of an acid catalyst such as an inorganic acid or an organic acid. When 4,4'-bischloromethylbiphenyl is used, the reaction can also be carried out without a catalyst, but generally in order to suppress the side reactions such as the reaction of chloromethyl and hydroxyl groups to form ether bonds, it can be carried out in the presence of an acid catalyst. As the acid catalyst, it can be appropriately selected from well-known inorganic acids and organic acids, for example, mineral acids such as hydrochloric acid, sulfuric acid, and phosphoric acid, organic acids such as formic acid, oxalic acid, trifluoroacetic acid, p-toluenesulfonic acid, methanesulfonic acid, and trifluoromethanesulfonic acid, Lewis acids such as zinc chloride, aluminum chloride, ferric chloride, and boron trifluoride, or solid acids, etc.
[0087] Usually, the reaction is carried out at 100 to 250° C. for 1 to 20 hours, preferably at 100 to 180° C., more preferably at 140 to 180° C. If the reaction temperature is low, the reactivity is insufficient and the reaction time is required, while if the reaction temperature is high, the resin may decompose.
[0088] During the reaction, as a solvent, for example, alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol, methyl cellosolve, ethyl cellosolve, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and aromatic compounds such as benzene, toluene, chlorobenzene, and dichlorobenzene can be used, and among these, ethyl cellosolve, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, etc. are particularly preferred. After the reaction is completed, the obtained polyhydroxy resin can be desolventized by distillation under reduced pressure, washing with water, or reprecipitation in a poor solvent, but it can also be used as a raw material for epoxidation reaction in a state where the solvent remains.
[0089] The polyhydroxy resin of formula (1-3) thus obtained can be used as a raw material for epoxy resin and as a curing agent for epoxy resin. In addition, it can be used as a phenolic resin molding material by further combining it with a curing agent such as hexamine.
[0090] Next, the preparation method of the epoxy resin represented by formula (1-2) is not particularly limited, and it can be produced by reacting the raw material phenolic compound represented by the following formula (1-6) with epichlorohydrin. The reaction can be carried out in the same manner as a conventional epoxidation reaction. In addition, when the raw material is a mixture with a compound represented by formula (1-6) with p=0 or 1, the epoxy resin obtained by this preparation method, as described above, includes not only the epoxy resin of the first embodiment of the present invention, but also a mixture of the epoxy resin of the first embodiment of the present invention and the epoxide of the compound represented by the above general formula (1-2) with p=0 or 1.
[0091]
[0092] Here, Y, B and p in formula (1-6) are the same as those in the above formula (1-2).
[0093] The phenolic compound represented by formula (1-6) (including a mixture with a compound wherein p=0 or 1) preferably has a hydroxyl equivalent (g / eq) of 150 to 230, more preferably 170 to 220. The melting point is preferably 140 to 300°C, more preferably 150 to 250°C.
[0094] Here, the raw material phenolic compound represented by formula (1-6) is not limited in its preparation method as long as it has a specified structure, and can be appropriately obtained by reacting either or both of a benzonitrile compound and a dihaloalkyl compound with a dihydroxy compound having a Y group in formula (1-6) in the presence of a basic catalyst.
[0095] For example, as the benzonitrile compound, for example, 2,4-dichlorobenzonitrile, 2,5-dichlorobenzonitrile, 2,6-dichlorobenzonitrile, 3,5-dichlorobenzonitrile, 2,4-dibromobenzonitrile, 2,5-dibromobenzonitrile, 2,6-dibromobenzonitrile, 3,5-dibromobenzonitrile and the like can be mentioned; as the dihaloalkyl compound, for example, 1,3-dibromopropane, 1,4-dibromobutane, 1,5-dibromopentane, 1,6-dibromohexane and the like can be mentioned; as the dihydroxy compound having the Y group in formula (1-6), for example, 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxybenzophenone, bisphenol A, bisphenol F and the like can be mentioned.
[0096] There is no particular limitation on the method for producing the above-mentioned raw material phenolic compound, and more detailed specific conditions can be, for example, the method described in WO2021 / 201046.
[0097] For the reaction of the above-mentioned raw material phenolic compound and epichlorohydrin, for example, a method can be mentioned in which the phenolic compound is dissolved in an excess of epichlorohydrin, and then reacted at 50 to 150°C, preferably 60 to 100°C, for 1 to 10 hours in the presence of an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide. The amount of the alkali metal hydroxide used at this time is 0.8 to 2.0 mol, preferably 0.9 to 1.5 mol, relative to 1 mol of the hydroxyl group in the phenolic compound. Excess epichlorohydrin can be used relative to the hydroxyl group in the phenolic compound, usually 1.5 to 15 mol relative to 1 mol of the hydroxyl group in the phenolic compound. After the reaction is completed, the excess epichlorohydrin is distilled off, and the residue is dissolved in a solvent such as toluene or methyl isobutyl ketone, filtered, washed with water to remove the inorganic salt, and then the solvent is distilled off to obtain the target epoxy resin.
[0098] From the viewpoint of improving the reliability of the electronic components used, the purity of the epoxy resin, especially the amount of hydrolyzable chlorine, is as low as possible. Although not particularly limited, it is preferably 1000 ppm or less, and more preferably 500 ppm or less. It should be noted that the hydrolyzable chlorine in the first embodiment of the present invention refers to the value measured by the following method. That is, 0.5 g of the sample is dissolved in two After 30 ml of oxane, 10 ml of 1N-KOH was added, and the mixture was boiled and refluxed for 30 minutes, cooled to room temperature, and 100 ml of 80% acetone water was further added. The solution was potentiometrically titrated using 0.002N-AgNO3 aqueous solution to obtain the value.
[0099] As the curing agent used in the epoxy resin composition of the first embodiment of the present invention, materials generally known as curing agents for epoxy resins can be used, including dicyandiamide, acid anhydrides, polyphenols, aromatic and aliphatic amines, etc. Among these, polyphenols are preferably used as curing agents in fields requiring high electrical insulation such as semiconductor packaging materials. Specific examples of curing agents are shown below.
[0100] Examples of polyphenols include dihydric phenols such as bisphenol A, bisphenol F, bisphenol S, fluorene bisphenol, 4,4'-biphenol, 2,2'-biphenol, hydroquinone, resorcinol, and naphthalene diol, or trihydric or higher phenols represented by tris(4-hydroxyphenyl)methane, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, phenol novolac, o-cresol novolac, naphthol novolac, and polyvinylphenol. Furthermore, polyphenolic compounds synthesized from dihydric phenols such as phenols, naphthols, bisphenol A, bisphenol F, bisphenol S, fluorene bisphenol, 4,4'-biphenol, 2,2'-biphenol, hydroquinone, resorcinol, and naphthalene diol with condensation agents such as formaldehyde, acetaldehyde, benzaldehyde, p-hydroxybenzaldehyde, and p-phenylenediol.
[0101] Examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, dodecylsuccinic anhydride, nadic anhydride, and trimellitic anhydride.
[0102] Examples of the amine curing agent include aromatic amines such as 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylsulfone, m-phenylenediamine, and p-phenylenediamine, and aliphatic amines such as ethylenediamine, hexamethylenediamine, diethylenetriamine, and triethylenetetramine.
[0103] These curing agents may be used alone or in combination of two or more.
[0104] The mixing ratio of epoxy resin to curing agent is preferably in the range of 0.8 to 1.5 in terms of the equivalent ratio of epoxy group to functional group in the curing agent. Outside this range, unreacted epoxy groups or functional groups in the curing agent may remain after curing, which may reduce the reliability related to the packaging function.
[0105] In the epoxy resin composition of the first embodiment of the present invention, polyester, polyamide, polyimide, polyether, polyurethane, petroleum resin, indene resin, indene coumarin resin, phenoxy resin and other oligomers or polymer compounds can be appropriately blended as other modifiers, etc. The added amount is usually in the range of 1 to 30 parts by weight relative to 100 parts by weight of the total resin components.
[0106] In the epoxy resin composition of the first embodiment of the present invention, inorganic fillers, pigments, flame retardants, thixotropy imparting agents, coupling agents, fluidity improvers and other additives other than the above-mentioned layered clay minerals such as mica and talc can be added. As inorganic fillers, for example, spherical or crushed fused silica, crystalline silica and other silica powders, alumina powders, glass powders or calcium carbonate, alumina, hydrated alumina, etc. can be cited. The preferred amount of use when used for semiconductor packaging materials is 70% by weight or more, and more preferably 80% by weight or more. The preferred amount of use when used for heat dissipation substrates is 20 to 90% by weight, and more preferably 40 to 60% by weight, because fluidity is required.
[0107] Examples of the pigment include organic or inorganic extender pigments, flaky pigments, etc. Examples of the thixotropy-imparting agent include silicone-based, castor oil-based, aliphatic amide waxes, oxidized polyethylene waxes, and organic bentonite-based agents.
[0108] In the epoxy resin composition of the first embodiment of the present invention, a curing accelerator can be used as needed. For example, there are amines, imidazoles, organic phosphines, Lewis acids, etc., specifically, tertiary amines such as 1,8-diazabicyclo (5,4,0) undecene-7, triethylenediamine, benzyldimethylamine, triethanolamine, dimethylaminoethanol, tris (dimethylaminomethyl) phenol, 2-methylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-phenyl-4-methylimidazole, 2-heptadecylimidazole, etc., organic phosphines such as tributylphosphine, methyldiphenylphosphine, triphenylphosphine, diphenylphosphine, phenylphosphine, tetraphenylphosphine, etc. Tetraphenylborate, tetraphenyl ·Ethyl triphenyl borate, tetrabutyl Tetrabutyl borate and other tetrasubstituted Tetrasubstituted borate, tetraphenyl borate such as 2-ethyl-4-methylimidazole tetraphenyl borate and N-methylmorpholine tetraphenyl borate, etc. The amount added is usually in the range of 0.01 to 5 parts by weight based on 100 parts by weight of the total resin component.
[0109] Furthermore, the epoxy resin composition of the first embodiment of the present invention may contain, as necessary, a release agent such as carnauba wax and OP wax, a coupling agent such as γ-glycidoxypropyltrimethoxysilane, a colorant such as carbon black, a flame retardant such as antimony trioxide, a stress reducing agent such as silicone oil, a lubricant such as calcium stearate, and the like.
[0110] The epoxy resin composition of the first embodiment of the present invention can be made into a varnish state in which an organic solvent is dissolved, and then impregnated into a fibrous material such as glass cloth, aramid nonwoven fabric, polyester nonwoven fabric such as liquid crystal polymer, and then the solvent is removed to make a prepreg. In addition, it can be coated on a sheet such as copper foil, stainless steel foil, polyimide film, polyester film, etc. to make a laminated product.
[0111] If the epoxy resin composition of the first embodiment of the present invention is heat-cured, the resin cured product of the first embodiment of the present invention can be prepared. The cured product can be obtained by molding the epoxy resin composition by casting, compression molding, transfer molding and the like. The temperature at this time is usually in the range of 120 to 220°C. Furthermore, the thermal conductivity of the molded product with a crystallinity of more than 10% is high, and it is suitable for high thermal conductivity applications such as heat dissipation substrates. In addition, the crystallinity is affected by the temperature control during molding. If it is molded at a high temperature exceeding 200°C, it becomes amorphous, and it is difficult to obtain a molded product in which the crystallinity can be observed. It is preferably heated in stages. It is more preferably molded by heating in stages at a temperature of 120 to 200°C for 30 seconds to 1 hour (preferably 1 minute to 30 minutes). In addition, after molding, the above-mentioned crystallinity can be adjusted by post-curing. The post-curing temperature is 130°C to 250°C, and the time is in the range of 1 hour to 24 hours. It is preferably post-cured at a temperature 5°C to 40°C lower than the endothermic peak temperature measured using the differential scanning calorimeter and conditions shown in the examples for 1 hour to 24 hours. It should be noted that the crystallinity of the molded product (cured product) can be obtained based on the ratio of the crystallinity peak by the method described in the examples.
[0112] <Second embodiment>
[0113] The second embodiment of the present invention will be described in detail below.
[0114] The second embodiment of the present invention relates to a vinyl resin composition using a vinyl resin as a crystalline resin. In the second embodiment, the vinyl resin used in the vinyl resin composition adopts a resin having crystallinity at room temperature, and its melting point is greater than 80°C and below 200°C as described above. Preferably, the melting point ranges from 90 to 200°C, and more preferably from 110 to 180°C. As described above, the melting point refers to the endothermic peak temperature accompanying the melting of the crystal in differential scanning calorimetry. Vinyl resins having a melting point higher than 200°C tend to have strong crystallinity, reduced solvent solubility, and melt kneading properties, and cured products using vinyl resins having a melting point lower than 90°C tend not to have improved thermal conductivity.
[0115] The vinyl equivalent of the vinyl resin used in the second embodiment of the present invention is preferably in the range of 150 to 1000 g / eq. More preferably, it is in the range of 200 to 500 g / eq. If it is larger than this range, the reactivity tends to be lowered, unreacted components are generated during curing, and there is a tendency for heat resistance and reliability to decrease. If it is smaller than this range, the solvent solubility and melt kneading properties decrease, and the cured product tends to become hard and brittle, and the film properties tend to decrease.
[0116] Regarding the polar group of the vinyl resin used in the second embodiment of the present invention, the hydroxyl equivalent is preferably 5000 g / eq or more, and the total chlorine content is preferably 2000 ppm or less.
[0117] The vinyl resin used in the second embodiment of the present invention can be obtained by reacting the hydroxyl group of the hydroxyl resin with an aromatic vinylating agent represented by chloromethylstyrene, but at this time, the hydroxyl group of the hydroxyl resin that remains unreacted is large, and when the hydroxyl equivalent is less than 5000g / eq, there is a tendency that the curing becomes insufficient, and the thermal conductivity and heat resistance decrease. In addition, since the hydroxyl group is a polar group, its residue has a tendency to hinder the reduction of the dielectric constant and the dielectric loss tangent. The hydroxyl equivalent is more preferably 8000g / eq or more, and more preferably 10000g / eq or more.
[0118] On the other hand, as chlorine components, there are chlorine components from chloromethylstyrene and chlorine components from crosslinking agents in the raw materials for manufacturing hydroxy resins. When the solvent solubility of the vinyl resin is low, it is difficult to remove these chlorine components. When the residual chlorine component is more than 2000ppm, there is a tendency to reduce thermal conductivity and heat resistance due to hindering the reduction of dielectric constant and dielectric loss tangent and hindering the curing reaction. The total chlorine content is more preferably less than 1000ppm, and more preferably less than 800ppm.
[0119] The vinyl resin used in the second embodiment of the present invention can be appropriately obtained by reacting a hydroxy resin (hydroxy compound) with an aromatic vinylating agent. Although not limited, for example, a vinyl resin having a structure represented by the following formula (2-1) to (2-3) can be preferably cited. The structure of the following formula (2-1) to (2-3) is a structural skeleton that can suppress the molecular mobility within and between molecules and can be expected to have thermal conductivity, and has good solvent solubility and melt kneading properties, so a uniform cured product can be formed and thermal conductivity can be exhibited, so it is a preferred embodiment as a resin for achieving the purpose of the present invention.
[0120] <Vinyl resin of formula (2-1)>
[0121] The vinyl resin represented by the above formula (2-1) can be obtained by reacting the hydroxy resin (hydroxy compound) represented by the general formula (2-4) with chloromethylstyrene. This reaction can be carried out in the same manner as a known vinylation reaction.
[0122]
[0123] R in formula (2-4) 1 ~R 6 Same as formula (2-1).
[0124] In formula (2-1) and formula (2-4), R 1 ~R 6 Each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms. From the viewpoint of solvent solubility, an alkyl group is preferred, and from the viewpoint of heat resistance and high thermal conductivity, an aromatic group is preferred. Alkyl groups having more than 6 carbon atoms are difficult to inhibit molecular motion, and there is also a concern that compatibility may be reduced. In addition, a bulky structure with large steric hindrance may have a concern of decreased solvent solubility due to increased crystallinity. A more preferred structure is a methyl group or a phenyl group. In formula (2-1) and formula (2-4), R 1 ~R 6 It can be a mixture of different structures.
[0125] The substitution position of the vinyl benzyl ether in the vinyl resin of formula (2-1) is not particularly limited, but is preferably para-positioned relative to the methine groups connecting three aromatic rings from the viewpoint of thermal conductivity and heat resistance. It is particularly preferred that all three vinyl benzyl ethers are para-positioned.
[0126] The number average molecular weight (Mn) of the vinyl resin of formula (2-1) is preferably 2000 or less, more preferably 1500 or less. In addition, it may also contain a multi-branched body represented by the following general formula (2-5). In formula (2-5), t is the number of repetitions (number average), representing a number from 0 to 20. It is preferably a mixture of components with different values of t. From the viewpoint of thermal conductivity, the content of t=0 body is preferably 50 weight % (wt%) or more, more preferably 80 wt% or more.
[0127]
[0128] The hydroxyl equivalent of the trifunctional hydroxy compound of formula (2-4) is preferably 90 to 350 g / eq, more preferably 100 to 200 g / eq. The trifunctional hydroxy compound of formula (2-4) can be produced by a common method, for example, by polycondensing a monophenol compound with an aromatic aldehyde.
[0129] Examples of the monohydric phenol compound include monoalkylphenols such as phenol, o-cresol, m-cresol, p-cresol, o-ethylphenol, m-ethylphenol, p-ethylphenol, p-octylphenol, p-tert-butylphenol, o-cyclohexylphenol, m-cyclohexylphenol, and p-cyclohexylphenol; dialkylphenols such as 2,5-xylenol, 3,5-xylenol, 3,4-xylenol, 2,4-xylenol, and 2,6-xylenol; trialkylphenols such as 2,3,5-trimethylphenol and 2,3,6-trimethylphenol; and hydroxybiphenyls such as 2-phenylphenol, 4-phenylphenol, 3-benzyl-1,1'-biphenyl-2-phenol, 3-benzyl-1,1'-biphenyl-4-phenol, 3-phenylphenol, and 2,6-diphenylphenol. In view of solvent solubility, reactivity, and supplyability, 2,5-dimethylphenol, 2,6-dimethylphenol, and 2-phenylphenol are particularly preferred. These phenol compounds may be used alone or in combination of two or more.
[0130] Examples of the aromatic aldehyde include hydroxybenzaldehydes such as 2-hydroxybenzaldehyde, 3-hydroxybenzaldehyde, 4-hydroxybenzaldehyde, 4-hydroxy-3-methylbenzaldehyde, 4-hydroxy-3,5-dimethylbenzaldehyde, 4-hydroxy-2,5-dimethylbenzaldehyde, and 3,5-diethyl-4-hydroxybenzaldehyde. From the viewpoint of heat resistance and thermal conductivity, 4-hydroxybenzaldehyde is preferred.
[0131] The polycondensation of phenolic compounds and aromatic aldehydes can use an acid catalyst, for example, acetic acid, oxalic acid, sulfuric acid, hydrochloric acid, phenolsulfonic acid, p-toluenesulfonic acid, zinc acetate, manganese acetate etc. can be enumerated. These acid catalysts can use only one kind, and can also use more than two kinds. In addition, among these acid catalysts, preferred sulfuric acid and p-toluenesulfonic acid are from the aspect of excellent activity. It should be noted that the acid catalyst can be added before the reaction, and can also be added midway in the reaction.
[0132] The polycondensation of phenolic compounds and aromatic aldehydes can be carried out in the presence of a solvent to obtain a polycondensate as needed. Examples of the solvent include monohydric alcohols such as methanol, ethanol, and propanol; polyhydric alcohols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, propylene glycol, diethylene glycol, polyethylene glycol, and glycerol; dihydric alcohol ethers such as 2-ethoxyethanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monopentyl ether, ethylene glycol dimethyl ether, ethylene glycol methyl ethyl ether, and ethylene glycol monophenyl ether; and dihydric alcohol ethers such as 1,3-diol. Alkane, 1,4-di Cyclic ethers such as alkanes and tetrahydrofuran; glycol esters such as ethylene glycol acetate; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, etc. These solvents may be used alone or in combination of two or more. Among these solvents, 2-ethoxyethanol is preferred from the perspective of excellent solubility of the obtained compound.
[0133] The reaction temperature during the polycondensation of the phenol compound and the aromatic aldehyde is preferably in the range of 20 to 140°C, more preferably in the range of 80 to 110°C.
[0134] The charging ratio of the phenol compound / aromatic aldehyde is preferably in the range of 1 / 0.1 to 1 / 0.5, more preferably 1 / 0.3 to 1 / 0.5 in terms of molar ratio, from the viewpoint of easily removing the phenol compound after the reaction by reprecipitation or the like.
[0135] The vinyl resin of formula (2-1) can be suitably obtained by reacting a trifunctional hydroxy compound with an aromatic vinylating agent. Although not limited thereto, for example, a suitable vinyl resin in the present invention represented by the above formula (2-1) can be obtained by reacting a trifunctional hydroxy compound represented by the above formula (2-4) with chloromethylstyrene. The reaction can be carried out in the same manner as a known vinylation reaction.
[0136] Regarding the mixing ratio, the aromatic vinylating agent (e.g., chloromethylstyrene) is preferably used in an amount of 0.8 to 1.2 equivalents per 1.0 equivalent of the hydroxyl group as the functional group of the trifunctional hydroxy compound. However, when the reactivity of the trifunctional hydroxy compound is low, an excess amount of the aromatic vinylating agent may be added and removed after the reaction.
[0137] As the aromatic vinylating agent, halomethylstyrene is preferred, and chloromethylstyrene is particularly preferred. In addition, bromomethylstyrene and its isomers, and substances having substituents can be cited. The substitution position of the halomethyl form is preferably the 4-position in the case of halomethylstyrene, and the 4-position form is preferably 60% by weight or more of the whole.
[0138] The reaction of the trifunctional hydroxy compound and the aromatic vinylating agent can be carried out in the absence of a solvent or in the presence of a solvent. An aromatic vinylating agent can be added to the hydroxy compound, and a metal hydroxide can be added to react, and the generated metal salt can be removed by filtering, washing with water, etc. to react. Solvents include methyl ethyl ketone, benzene, toluene, xylene, methyl isobutyl ketone, diethylene glycol dimethyl ether, cyclopentanone, cyclohexanone, etc., but are not limited to these. From the viewpoint of reactivity, methyl ethyl ketone is preferred. As specific examples of metal hydroxides, sodium hydroxide, potassium hydroxide, etc. can be mentioned, but are not limited to these.
[0139] The vinylation reaction is preferably carried out at a temperature of 90° C. or less, more preferably at a temperature of 70° C. or less. At a temperature higher than this, the vinyl benzyl ether may be heated to self-polymerize, making it difficult to control the reaction. In order to suppress self-polymerization, a polymerization inhibitor such as quinones, nitro compounds, nitrophenols, nitroso, nitrone compounds, oxygen, etc. may be used.
[0140] The reaction endpoint can be determined by tracking the residual amount of halomethylstyrene as an aromatic vinylating agent using various chromatography methods such as GPC, and the reaction rate can be adjusted by the type, amount, addition rate, solid content concentration, etc. of the metal hydroxide.
[0141] <Vinyl resin of formula (2-2), vinyl resin of formula (2-3)>
[0142] As the vinyl resin used in the second embodiment of the present invention, in addition to the vinyl resin represented by formula (2-1), vinyl resins represented by formulas (2-2) and (2-3) are also preferred. These vinyl resins can be used in combination, preferably containing more than 50wt% of the vinyl resin represented by formulas (2-1) to (2-3) of the entire resin component. It is further preferred to contain more than 70wt%. If the proportion used is less than this, sometimes the effect of improving the heat resistance, thermal conductivity, etc. when the cured product is made is small.
[0143] [Vinyl resin of formula (2-2)]
[0144] In the above formula (2-2), n is a repeating number (number average), which is 0 to 20. Usually, it is a mixture of components having different repeating numbers (n), and the average value (number average) of n is preferably in the range of 0.1 to 15, and more preferably in the range of 0.5 to 10.
[0145] A independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO- or a divalent hydrocarbon group having 1 to 6 carbon atoms, and X independently represents a benzene ring, a naphthalene ring or a biphenyl ring. From the viewpoint of thermal conductivity, it is preferred that A is a single bond and X is a biphenyl ring. The substitution positions of the two vinyl benzyl ether groups bonded to the biphenyl structure having A preferably include at least 2,2'. In formula (2-2), when A is a single bond, that is, when both ends are biphenyl rings, the substitution positions of the two vinyl benzyl ether groups bonded thereto are preferably 4,4' and 2,2', and the ratio of the biphenyls at both ends is preferably 2,2' of the whole 40 to 90 mol%. When A is other than a single bond, that is, when both ends of the vinyl resin are other than biphenyl rings, such as a diphenylmethane structure, the substitution positions of the two vinyl benzyl ether groups bonded thereto are preferably 4,4' at 30 to 100 mol%.
[0146] The vinyl resin of formula (2-2) is preferably a polyfunctional vinyl resin represented by the following formula (2-6).
[0147]
[0148] In formula (2-6), e and f are repetition numbers (number average), which represent numbers from 0 to 20. Preferably, it is a mixture of components having different values of e and f. The ratio (molar ratio) of e / (e+f) is preferably from 0.50 to 0.95, and more preferably from 0.70 to 0.95. When it is less than 0.50, the effects of heat resistance and high thermal conductivity tend to be small, and when it is greater than 0.95, the crystallinity tends to become stronger and the solvent solubility tends to decrease. The average value of e is preferably from 0.1 to 10, and more preferably from 0.5 to 5. The average value of f is preferably from 0.1 to 5, and more preferably from 0.1 to 2.
[0149] A is the same as that in the above formula (2-2).
[0150] The polyfunctional vinyl resin represented by the above formula (2-6) can be produced by reacting a polyvalent hydroxy resin represented by the formula (2-7) with chloromethylstyrene.
[0151]
[0152] In the polyhydroxy resin of formula (2-7), the ratios of A, e, f, and e / (e+f) are the same as those of the polyfunctional vinyl resin of formula (2-6). The hydroxyl equivalent of the polyhydroxy resin represented by formula (2-6) is preferably 100 to 350 g / eq. The polyfunctional vinyl resin represented by formula (2-6) can be obtained by vinylizing part or all of these hydroxyl groups.
[0153] The polyhydroxy resin of formula (2-7) is not limited and can be produced, for example, as shown in the following formula (2-11), by reacting 4,4'-dihydroxybiphenyl represented by formula (2-8) with an aromatic crosslinking agent having a biphenyl structure represented by formula (2-9) and then reacting with a difunctional phenol compound represented by formula (2-10).
[0154]
[0155] Here, Z in the formula (2-9) represents a hydroxyl group, a halogen atom, or an alkoxy group having 1 to 6 carbon atoms.
[0156]
[0157] Here, A represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO-, or a divalent hydrocarbon group having 1 to 6 carbon atoms.
[0158]
[0159] With respect to the molar ratio of 4,4'-dihydroxybiphenyl represented by formula (2-8) and the difunctional phenol compound represented by formula (2-10) when the synthetic raw materials are added, 4,4'-dihydroxybiphenyl is preferably in the range of 0.50 to 0.95, and more preferably in the range of 0.70 to 0.95. When the ratio of 4,4'-dihydroxybiphenyl is less than this range, there is a tendency that heat resistance and high thermal conductivity are insufficient, while when it is more than this range, there is a tendency that solvent solubility decreases due to strong crystallinity.
[0160] The difunctional phenol compound of formula (2-10) is specifically 2,2'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxybenzophenone, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfide, dihydroxydiphenylmethanes, and 2,2-bis(4-hydroxyphenyl)propane. In particular, 2,2'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, and dihydroxydiphenylmethanes are preferred from the perspective of solvent solubility. Dihydroxydiphenylmethanes may be a mixture of ortho, meta, and para, and the isomer ratio of 4,4'-dihydroxydiphenylmethane is preferably 40% or less. If there is a large amount of 4,4'-dihydroxydiphenylmethane, there is a concern that the crystallinity is strong and the solvent solubility is reduced.
[0161] In the aromatic crosslinking agent represented by the above formula (2-9), Z represents a hydroxyl group, a halogen atom, or an alkoxy group having 1 to 6 carbon atoms. Specific examples of the aromatic crosslinking agent include 4,4'-bishydroxymethylbiphenyl, 4,4'-bischloromethylbiphenyl, 4,4'-bisbromomethylbiphenyl, 4,4'-bismethoxymethylbiphenyl, and 4,4'-bisethoxymethylbiphenyl. From the viewpoint of reactivity, 4,4'-bishydroxymethylbiphenyl or 4,4'-bischloromethylbiphenyl is preferred, and from the viewpoint of reducing ionic impurities, 4,4'-bishydroxymethylbiphenyl or 4,4'-bismethoxymethylbiphenyl is preferred.
[0162] The molar ratio of the phenols and aromatic crosslinking agents when reacting as shown in formula (2-11) is generally in the range of 0.2 to 0.7 moles of aromatic crosslinking agents per 1 mole of phenols, and more preferably in the range of 0.4 to 0.7 moles. If it is less than 0.2 moles, the ratio of n=0 in the obtained polyhydroxy resin represented by formula (2-2) is high, and especially when there are many 4,4'-dihydroxybiphenyl represented by formula (2-8), there is a concern that the solubility such as crystallinity will decrease. On the other hand, if it is more than 0.7 moles, the high molecular weight component becomes more, and it is sometimes difficult to manufacture stably.
[0163] The reaction of phenols with aromatic crosslinking agents can be carried out without a catalyst or in the presence of an acid catalyst such as an inorganic acid or an organic acid. When using 4,4'-bischloromethylbiphenyl, the reaction can also be carried out without a catalyst, but generally in order to suppress the side reactions such as the ether bond produced by the reaction of chloromethyl with hydroxyl groups, it can be carried out in the presence of an acid catalyst. As the acid catalyst, it can be appropriately selected from well-known inorganic acids and organic acids, for example, mineral acids such as hydrochloric acid, sulfuric acid, and phosphoric acid, organic acids such as formic acid, oxalic acid, trifluoroacetic acid, p-toluenesulfonic acid, methanesulfonic acid, and trifluoromethanesulfonic acid, Lewis acids or solid acids such as zinc chloride, aluminum chloride, ferric chloride, and boron trifluoride can be cited.
[0164] Usually, the reaction is carried out at 100 to 250° C. for 1 to 20 hours, preferably at 100 to 180° C., more preferably at 140 to 180° C. If the reaction temperature is low, the reactivity is insufficient and the reaction time is required, while if the reaction temperature is high, the resin may decompose.
[0165] During the reaction, as a solvent, for example, alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol, methyl cellosolve, ethyl cellosolve, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and aromatic compounds such as benzene, toluene, chlorobenzene, and dichlorobenzene can be used, and among these, ethyl cellosolve, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, etc. are particularly preferred. After the reaction is completed, the obtained polyhydroxy resin can be desolventized by distillation under reduced pressure, washing with water, or reprecipitation in a poor solvent, but it can also be used as a raw material for vinylation reaction in a state where the solvent remains.
[0166] The vinyl resin of formula (2-2), preferably the polyfunctional vinyl resin represented by formula (2-6), can be suitably obtained by reacting a polyhydroxy resin with an aromatic vinylating agent. For example, the polyfunctional vinyl resin represented by the above formula (2-6) can be obtained by reacting a polyhydroxy resin represented by the above formula (2-7) with chloromethylstyrene. The reaction can be carried out in the same manner as the known vinylation reaction.
[0167] The mixing ratio, type of aromatic vinylating agent, reaction conditions, confirmation of reaction end point and other aspects may be the same as those in the case of obtaining the vinyl resin of the above formula (2-1).
[0168] [Vinyl resin of formula (2-3)]
[0169] In the above formula (2-3), Y independently represents a direct bond, an oxygen atom, a sulfur atom, -SO2-, -CO-, -COO-, -CONH-, -CH2- or -C(CH3)2-. B independently represents a benzonitrile structure or -(CH2) q-, preferably contains a benzonitrile structure in at least one molecule. More preferably, contains a benzonitrile structure and -(CH2) in at least one molecule q -these two structures. q represents a number from 3 to 10. From the aspect of high thermal conductivity, Y is preferably a directly bonded biphenyl structure, -SO2-, -CO-, -COO- or -CONH-, more preferably a directly bonded biphenyl structure, among which the biphenyl structure at the 4,4' position is particularly preferred. On the other hand, from the aspect of moldability and solvent solubility, oxygen atoms, sulfur atoms, -CH2-, -C(CH3)2- are preferred. As indicated by "independently", the vinyl resin of formula (2-3) can be a mixture of structures with different Ys, and high thermal conductivity, moldability, and solvent solubility can be adjusted. p is a repetition number, representing a number from 0 to 15. Preferably, it can represent a number from 1 to 15. Preferably, it is a mixture of components with different p values. As a p value (average value), it is preferably 1.0 to 3.0, and more preferably 1.5 to 2.5.
[0170] The vinyl resin of formula (2-3) may be a mixture with a compound in which p=0, and the compound in which p=0 is preferably 40% or less in terms of area % measured by gel permeation chromatography (GPC area %). More preferably, it is 35% or less. When more than 40% of the compound in which p=0 is contained, there is a tendency that the crystallinity is strong, the melting point exceeds 200°C, and the solvent solubility also decreases. In addition, the reactivity of the compound in which p is greater than 15 is low, and if unreacted components are generated during curing, there is a tendency that the heat resistance decreases.
[0171] B represents a benzonitrile structure or -(CH2) q - alkyl structure. Preferably, at least one molecule contains a benzonitrile structure, and more preferably at least one molecule contains a benzonitrile structure and -(CH2) q - represents the structure of both alkyl structures. That is, B is also shown as "independently", and the vinyl resin of formula (2-3) can be a mixture of different structures of B, which can adjust high thermal conductivity, moldability, and solvent solubility. For B, it is preferred to contain 50 mol% or more, and more preferably 70 mol% or more of benzonitrile structure. The ratio of benzonitrile structure to alkyl structure is based on the mass of the raw material compound, and the alkyl structure is preferably less than 50 mol%, and more preferably 10 mol% to 40 mol%. When the alkyl structure is more than 50 mol%, the thermal conductivity and heat resistance of the cured product are easily reduced. When the alkyl structure is not included, the crystallinity tends to become stronger and the solvent solubility tends to decrease.
[0172] For -(CH2) q - represents an alkyl structure, q represents a repetition number, and represents a number of 3 to 10. More preferably, it is a number of 4 to 8. If it is less than 3, there is a tendency that the flexibility is low and the relaxation effect of crystallinity is low. If it is greater than 10, there is a tendency that the thermal conductivity and heat resistance of the cured product are greatly reduced.
[0173] Specifically, a vinyl resin represented by the following formula (2-12) can be preferably exemplified.
[0174]
[0175] (wherein g and h each independently represent a number from 1 to 15, and q represents a number from 3 to 10)
[0176] The vinyl resin of formula (2-3) can be suitably obtained by reacting a hydroxy resin with an aromatic vinylating agent. For example, the vinyl resin of the present invention represented by the above formula (2-3) can be obtained by reacting a hydroxy resin represented by general formula (2-13) with chloromethylstyrene. The reaction can be carried out in the same manner as the known vinylation reaction.
[0177] The mixing ratio, type of aromatic vinylating agent, reaction conditions, confirmation of reaction end point and other aspects may be the same as those in the case of obtaining the vinyl resin of the above formula (2-1).
[0178]
[0179] (wherein, Y independently represents a direct bond, an oxygen atom, a sulfur atom, -SO2-, -CO-, -COO-, -CONH-, -CH2- or -C(CH3)2-. B independently represents a benzonitrile structure or -(CH2) q -, preferably at least one of them contains a benzonitrile structure. More preferably, at least one molecule contains a benzonitrile structure and -(CH2) q - represents an alkyl structure. p and q are each independently a number from 0 to 15 and q represents a number from 3 to 10)
[0180] The hydroxy resin represented by formula (2-13) (including a mixture with a compound of p=0) preferably has a hydroxy equivalent (g / eq) of 150 to 300, more preferably 200 to 270. The number average molecular weight (Mn) is preferably 350 to 800, more preferably 450 to 600.
[0181] p is synonymous with p in the vinyl resin of formula (2-3), is a repeating number, and is a number of 0 to 15. Preferably, it is a number of 1 to 15. A mixture of components having different p values is preferred. The p value (average value) is preferably 1.0 to 3.0, and more preferably 1.5 to 2.5.
[0182] The hydroxy resin (phenolic compound) represented by formula (2-13) is not limited in its preparation method as long as it has a predetermined structure, and can be appropriately obtained by reacting either or both of a benzonitrile compound and a dihaloalkyl compound with a dihydroxy compound having a Y group in the presence of a basic catalyst.
[0183] At this time, examples of the benzonitrile compound include 2,4-dichlorobenzonitrile, 2,5-dichlorobenzonitrile, 2,6-dichlorobenzonitrile, 3,5-dichlorobenzonitrile, 2,4-dibromobenzonitrile, 2,5-dibromobenzonitrile, 2,6-dibromobenzonitrile, and 3,5-dibromobenzonitrile. Examples of the dihaloalkyl compound include 1,3-dibromopropane, 1,4-dibromobutane, 1,5-dibromopentane, and 1,6-dibromohexane. Examples of the dihydroxy compound having a Y group include 4,4′-dihydroxybiphenyl, 4,4′-dihydroxydiphenyl ether, 4,4′-dihydroxydiphenyl sulfide, 4,4′-dihydroxydiphenyl sulfone, 4,4′-dihydroxybenzophenone, bisphenol A, and bisphenol F.
[0184] Regarding the method for preparing the hydroxy resin (phenolic compound), more detailed specific conditions can be referred to, for example, WO2021 / 201046.
[0185] The vinyl resin used in the second embodiment of the present invention can be cured alone, but it is also preferably used as a vinyl resin composition that is mixed with various other additives in addition to the above-mentioned layered clay minerals such as talc and mica. As one of the other additives, in order to promote curing, a free radical polymerization initiator such as an azo compound or an organic peroxide can be mixed to make it cure. The free radical polymerization initiator can be mixed in a range of, for example, 0.01 to 10 parts by weight relative to 100 parts by weight of the vinyl resin.
[0186] The vinyl resin composition of the second embodiment of the present invention includes a vinyl resin and a layered clay mineral as an additive as essential components, but may be mixed with other vinyl compounds and other thermosetting resins, such as epoxy resins, oxetane resins, maleimide resins, acrylate resins, polyester resins, polyurethane resins, polyphenylene ether resins, benzoic acid resins, etc. Azine resin, etc.
[0187] In order to improve the thermal conductivity, for example, an inorganic filler other than the above-mentioned layered clay minerals, such as glass cloth, carbon fiber, alumina, and boron nitride, may be added.
[0188] In order to impart higher thermal conductivity, the inorganic filler preferably has high thermal conductivity. The thermal conductivity is preferably 20 W / m·K or more, more preferably 30 W / m·K or more, and further preferably 50 W / m·K or more. Moreover, at least a portion of the inorganic filler, preferably more than 50 wt%, has a thermal conductivity of 20 W / m·K or more. Moreover, the average thermal conductivity of the inorganic filler as a whole is increasingly better in the order of 20 W / m·K or more, 30 W / m·K or more, and 50 W / m·K or more.
[0189] Examples of inorganic fillers having such thermal conductivity include boron nitride, aluminum nitride, silicon nitride, silicon carbide, titanium nitride, zinc oxide, tungsten carbide, aluminum oxide, magnesium oxide and other inorganic powder fillers. The content of the inorganic filler in the vinyl resin composition of the second embodiment of the present invention is preferably 70% by weight or more when used for semiconductor packaging materials, and more preferably 80% by weight or more. The preferred amount when used for heat dissipation substrates is 20 to 90% by weight, and more preferably 40 to 60% by weight, because fluidity is required.
[0190] In order to improve the adhesive force and the handling of the composition, various other additives may be used, for example, silane coupling agents, defoamers, internal mold release agents, flow regulators, etc. In addition, various known additives such as colorants, flame retardants, and thixotropy imparting agents may be used within the scope of the purpose of the present invention.
[0191] The vinyl resin composition of the present invention can be dissolved in a solvent such as toluene, xylene, acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc., and impregnated into a substrate such as glass fiber, carbon fiber, polyester fiber, polyamide fiber, alumina fiber, paper, etc., and then heated and dried to obtain a prepreg, and the prepreg is hot-pressed to obtain a cured product, etc.
[0192] Furthermore, the vinyl resin composition of the second embodiment of the present invention may be applied to a sheet such as copper foil, stainless steel foil, polyimide film, polyester film, etc. to form a laminate, or a heat-dried resin sheet may be heat-pressed to obtain a cured product.
[0193] Such a vinyl resin composition of the second embodiment of the present invention is suitable for providing a cured product with high thermal conductivity, that is, suitable for use as a cured product for providing high thermal conductivity. Here, when the cured product of the vinyl resin composition of the second embodiment of the present invention contains an inorganic filler, the thermal conductivity is preferably 8 W / m·K or more, more preferably 10 W / m·K or more. When no inorganic filler is contained, the thermal conductivity is preferably 0.25 W / m·K or more, more preferably 0.30 W / m·K or more.
[0194] Example
[0195] The present invention will be described in detail below with reference to Examples and Comparative Examples. However, the present invention is not limited thereto. Unless otherwise specified, "part" means part by weight and "%" means % by weight.
[0196] <Example of the first embodiment>
[0197] The first embodiment of the present invention will be described in more detail below with reference to examples.
[0198] Synthesis Example 1-1 (Manufacture of epoxy resin A)
[0199] 100.0 g of 4,4'-dihydroxydiphenyl ether was dissolved in 460 g of epichlorohydrin and 70 g of diethylene glycol dimethyl ether, and 90.8 g of 48% sodium hydroxide aqueous solution was added dropwise at 60°C and under reduced pressure (about 130 Torr) for 3 hours. During this period, the generated water was discharged from the system by azeotropy with epichlorohydrin, and the distilled epichlorohydrin was returned to the system. After the addition was completed, the reaction was continued for another hour, and after dehydration, epichlorohydrin was distilled off, and 580 g of toluene was added, and the salt was removed by washing with water. Thereafter, water was removed by separation, and toluene was distilled off under reduced pressure to obtain 126 g of white crystalline epoxy resin (epoxy resin A). The epoxy equivalent is 163, the hydrolyzable chlorine is 150 ppm, the melting point is 83°C, and the viscosity at 150°C is 10 mPa·s. The epoxy resin obtained from 4,4'-dihydroxydiphenyl ether had n=0 (monomer) of 91.2% as determined by GPC measurement, and n=1 or more was 8.8%.
[0200] Synthesis Example 1-2 (Manufacture of epoxy resin B)
[0201] 50.0 g of hydroquinone and 100.0 g of 4,4'-dihydroxybiphenyl were dissolved in 1000 g of epichlorohydrin and 150 g of diethylene glycol dimethyl ether, and 16.5 g of 48% sodium hydroxide was added at 60°C, and stirred for 1 hour. Thereafter, 148.8 g of 48% sodium hydroxide aqueous solution was added dropwise under reduced pressure (about 130 Torr) for 3 hours. During this period, the generated water was discharged out of the system by azeotropy with epichlorohydrin, and the distilled epichlorohydrin was returned to the system. After the addition was completed, the reaction was further continued for 1 hour, and after dehydration, epichlorohydrin was distilled off, and 600 g of methyl isobutyl ketone was added, and the salt was removed by washing with water. Thereafter, 13.5 g of 48% sodium hydroxide was added at 85°C, stirred for 1 hour, and washed with 200 mL of warm water. After that, after removing water by liquid separation, methyl isobutyl ketone was distilled off under reduced pressure to obtain 224 g of white crystalline epoxy resin (epoxy resin B). The epoxy equivalent is 139, the hydrolyzable chlorine is 320 ppm, the melting point is 125°C, and the viscosity at 150°C is 3.4 mPa·s. The n=0 (monomer) of the epoxy resin obtained from 4,4'-dihydroxybiphenyl determined by GPC is 67.2%. In addition. The n=0 (monomer) of the epoxy resin obtained from hydroquinone is 23.1%. n=1 or above is 9.7%.
[0202] Synthesis Example 1-3 (Manufacture of epoxy resin C)
[0203] After dissolving 115.7 g of 4,4'-dihydroxybiphenyl in 700 g of NMP in a 2L four-necked separable flask, 56.7 g of potassium carbonate was added, and the temperature was raised to 120°C while stirring under a nitrogen flow. Thereafter, 35.6 g of 2,6-dichlorobenzonitrile was added, and the temperature was raised to 145°C for reaction for 6 hours. After adding 49.2 g of acetic acid to the reaction solution for neutralization, NMP was distilled off under reduced pressure. After adding 500 mL of MIBK to the reaction solution to dissolve the product, the generated salt was removed by washing with water. Thereafter, MIBK was removed by reduced pressure distillation to obtain 129 g of hydroxy resin. The hydroxyl equivalent of the obtained hydroxy resin was 170 g / eq., and the melting point was 272°C. 50.0 g of the obtained hydroxy resin, 380 g of epichlorohydrin, and 96 g of diethylene glycol dimethyl ether (diglyme) were added, and 27.5 g of a 48.6% sodium hydroxide aqueous solution was added dropwise at 65°C for 3 hours under reduced pressure (about 130 Torr). During this period, the generated water was discharged from the system by azeotropy with epichlorohydrin, and the distilled epichlorohydrin was returned to the system. After the addition was completed, the reaction was continued for another hour and dehydration was performed. Thereafter, epichlorohydrin and diethylene glycol dimethyl ether were distilled off under reduced pressure, dissolved in 200 mL of methyl isobutyl ketone, and the generated salt was removed by filtration. Thereafter, 0.4 g of a 48% sodium hydroxide aqueous solution was added and reacted at 80°C for 2 hours. After the reaction, filtration and water washing were performed, and methyl isobutyl ketone as a solvent was distilled off under reduced pressure to obtain 43 g of epoxy resin (epoxy resin C) that was solid at room temperature. The obtained epoxy resin C had a melting point of 139° C., an epoxy equivalent of 226 g / eq., and a hydrolyzable chlorine content of 80 ppm.
[0204] Synthesis Example 1-4 (Manufacturing of Epoxy Resin D)
[0205] In a 1000ml four-necked flask, 77.5g of 4,4'-dihydroxybiphenyl, 119.3g of diethylene glycol dimethyl ether, and 41.8g of 4,4'-bischloromethyl biphenyl were added. Under a nitrogen stream, the temperature was raised to 160°C for reaction for 20 hours while stirring to generate a polyhydroxy resin with an OH equivalent of 135g / eq. After the reaction, 45.6g of diethylene glycol dimethyl ether was recovered, 455.1g of epichlorohydrin was added, and 70.5g of a 48% aqueous sodium hydroxide solution was added dropwise at 62°C for 4 hours under reduced pressure (about 130Torr). During this period, the generated water was discharged from the system by azeotropy with epichlorohydrin, and the distilled epichlorohydrin was returned to the system. After the addition was completed, the reaction was continued for another hour. Thereafter, epichlorohydrin was distilled off, methyl isobutyl ketone was added, and the salt was removed by water washing, followed by filtration and water washing, and then methyl isobutyl ketone was distilled off under reduced pressure to obtain 129 g of epoxy resin (epoxy resin D). The epoxy resin D had an epoxy equivalent of 200 g / eq, a softening point of 125° C., a melting point of 120° C., a melt viscosity of 0.21 Pa·s, and a hydrolyzable chlorine content of 230 ppm.
[0206] Examples 1-1 to 1-9, Comparative Examples 1-1 to 1-5
[0207] The epoxy resin obtained in Synthesis Example 1-1 (epoxy resin A), the epoxy resin obtained in Synthesis Example 1-2 (epoxy resin B), the epoxy resin obtained in Synthesis Example 1-3 (epoxy resin C), and the epoxy resin obtained in Synthesis Example 1-4 (epoxy resin D) were used as epoxy resins. 4,4'-dihydroxydiphenyl ether (curing agent A, OH equivalent 101 g / eq.), phenol novolac (curing agent B: Aica Industries, BRG-557, OH equivalent 105 g / eq., softening point 82°C) were used as curing agents, triphenylphosphine was used as a curing accelerator, spherical alumina (Denka, DAW-10, average particle size 12.2 μm) was used as an inorganic filler, and talc (additive A, average particle size 10 to 15 μm, Fujifilm) was used. As additives, additive C (1,3:2,4-bis(3,4-dimethylbenzylidene)-D-sorbitol, manufactured by Tokyo Chemical Industry) or additive D (sodium 2,4,8,10-tetra-tert-butyl-12H-dibenzo[d,g][1,3,2]dioxaphosphocine-6-acid salt 6-oxide, manufactured by Tokyo Chemical Industry) was used.
[0208] The components shown in Table 1 were mixed with a mixer, and then kneaded with a heating roller for about 5 minutes. The resultant was cooled and crushed to obtain epoxy resin compositions of Examples 1-1 to 1-9 and Comparative Examples 1-1 to 1-5, respectively. The epoxy resin composition was molded at 175°C for 5 minutes, and then post-cured at 180°C for 12 hours to obtain a cured molded product, and its physical properties were evaluated. The results are summarized in Table 1. It should be noted that the numbers of each component in Table 1 represent weight parts.
[0209] [evaluate]
[0210] (1) Thermal conductivity
[0211] The thermal conductivity was measured by a transient hot wire method using a thermal conductivity meter model LFA447 manufactured by NETZSCH.
[0212] (2) Determination of melting point and heat of fusion (DSC method)
[0213] The measurement was performed using a Hitachi High-Tech Science TG / DTA7300 differential scanning calorimeter with a sample weighing approximately 10 mg and a heating rate of 10°C / min under a nitrogen stream. When a cured product containing an inorganic filler was used as a sample, the heat of fusion was converted only to the resin component.
[0214] (3) Linear expansion coefficient, glass transition temperature
[0215] The linear expansion coefficient and the glass transition temperature were measured using a TMA7100 thermomechanical measuring apparatus manufactured by Hitachi High-Tech Science at a heating rate of 10°C / min.
[0216] (4) Water absorption
[0217] A disk having a diameter of 50 mm and a thickness of 3 mm was molded and post-cured, and then the weight change rate after moisture absorption at 85° C. and a relative humidity of 85% for 100 hours was measured.
[0218] (5) XRD measurement and calculation of crystallinity
[0219] XRD measurement was performed using RINT TTR3 manufactured by Rigaku Co., Ltd. The measurement conditions were as follows: diffraction angle 2θ: 10° to 30°, scanning speed: 0.25° / min, divergence slit: 1 / 2 degree, divergence vertical limiting slit: 10 mm, scattering slit: 1 / 2 degree, light receiving slit: 0.3 mm.
[0220] The crystallinity is calculated by the following formula, excluding the diffraction peak of talc observed in the region of 28° to 29°. When mica is used, the peak observed in the region of 6° to 8° is excluded. Here, the crystalline peak refers to a peak with a width of the diffraction peak of less than 5°, preferably less than 3°, i.e., a sharp peak, and the amorphous peak refers to a broad peak with a diffraction peak width of more than 8°.
[0221] Crystallinity = [Crystallinity peak area / (Crystallinity peak area+Amorphous peak area)] × 100
[0222] These results show that the epoxy resin compositions obtained in Examples have excellent thermal conductivity and are therefore suitable for power devices and automotive applications. It should be noted that when the epoxy resin compositions of Comparative Examples not containing the predetermined layered clay mineral were used, no crystalline peak was obtained, and an amorphous peak was obtained, so the crystallinity was 0%.
[0223] [Table 1]
[0224]
[0225] [Effects of the invention and industrial applicability of the first embodiment]
[0226] The epoxy resin combination exemplified in the first embodiment provides a cured molded product having excellent moldability and reliability, high thermal conductivity, low water absorption, low thermal expansion, high heat resistance, and excellent flame retardancy, and is suitable for use as an insulating material for electrical and electronic materials such as semiconductor packaging, laminated boards, and heat dissipation substrates, and can exhibit excellent high heat dissipation, high heat resistance, flame retardancy, and high dimensional stability. It is speculated that the reason for such a specific effect is that the layered clay mineral can improve the orientation of a specific epoxy resin cured product having a rigid structure such as a biphenyl structure.
[0227] <Example of the second embodiment>
[0228] Hereinafter, the second embodiment of the present invention will be described in more detail with reference to examples.
[0229] In addition, the measurement method was measured by the following method.
[0230] 1) OH equivalent (hydroxyl equivalent)
[0231] Using a potentiometric titration apparatus, the solvent was 1,4-dimethoxybenzyl alcohol. The alkane was acetylated with 1.5 mol / L acetyl chloride, the excess acetyl chloride was decomposed with water, and titrated with 0.5 mol / L potassium hydroxide.
[0232] 2) Vinyl equivalent
[0233] The sample is reacted with a Weiss solution (iodine chloride solution) and left in a dark place. Thereafter, the excess iodine chloride is reduced to iodine, and the iodine component is titrated with sodium thiosulfate to calculate the iodine value. The iodine value is converted into a vinyl equivalent.
[0234] 3) Total chlorine
[0235] After dissolving 1.0 g of the sample in 25 ml of butyl carbitol, 25 ml of 1N-KOH propylene glycol solution was added, and the mixture was heated under reflux for 10 minutes, cooled to room temperature, and 100 ml of 80% acetone water was further added. The solution was measured by potentiometric titration using 0.002N-AgNO3 aqueous solution.
[0236] 4) GPC determination
[0237] A device with columns (4 TSKgel SuperMultiporeHZ-N manufactured by Tosoh Corporation) connected in series on a main body (manufactured by Tosoh Corporation, HLC-8220GPC) was used, and the column temperature was 40°C. In addition, tetrahydrofuran (THF) was used as the eluent, and the flow rate was set to 0.35 mL / min, and a differential refractive index detector was used as the detector. The sample was measured using 50 μL of a solution obtained by dissolving 0.1 g of the sample in 10 mL of THF and filtering with a microfilter. Data processing used Tosoh Corporation's GPC-8020 Model II Version 6.00.
[0238] 5) Melting point, heat of fusion (DSC method)
[0239] The measurement was performed using a DSC7020 differential scanning calorimeter manufactured by Hitachi High-Tech Science using a sample accurately weighed in an amount of about 10 mg, under a nitrogen flow and at a temperature increase rate of 10°C / min.
[0240] 6) Solvent solubility (precipitation temperature)
[0241] 2 g of resin and 1 g of methyl ethyl ketone were weighed in a sample bottle, heated and dissolved, and then the temperature was slowly lowered in a thermostatic bath to measure the temperature in the bath where the resin precipitated. The higher the precipitation temperature (°C), the worse the solvent solubility.
[0242] 7) Glass transition point (Tg)
[0243] Tg was determined using a thermomechanical measuring apparatus (EXSTAR TMA / 7100 manufactured by Hitachi High-Tech Science Co., Ltd.) at a temperature increase rate of 10°C / min.
[0244] 8) 5% weight loss temperature (Td5), residual carbon rate
[0245] The 5% weight loss temperature (Td5) was measured using a thermogravimetric / differential thermal analyzer (EXSTAR TG / DTA7300 manufactured by Hitachi High-Tech Science) in a nitrogen atmosphere at a heating rate of 10°C / min. The weight loss at 700°C was also measured to calculate the residual carbon ratio.
[0246] 9) Thermal conductivity
[0247] The thermal conductivity was measured by a transient hot wire method using a NETZSCH LFA447 thermal conductivity meter.
[0248] 10) Dielectric constant and dielectric loss tangent
[0249] The measurement was performed in accordance with JIS C 2138. The measurement frequency is expressed as a value of 1 GHz.
[0250] 11) Field desorption ionization mass spectrometry (FD-MS)
[0251] The measurement was performed using a mass spectrometer JMS-T100GCV (manufactured by JEOL Ltd.). The sample was dissolved in acetone and subjected to the measurement.
[0252] (Synthesis example 2-1)
[0253] In a 1000 mL four-necked flask, 73.6 g (0.60 mol) of 2,5-dimethylphenol (the following structural formula 2-14) and
[0254]
[0255] p-Hydroxybenzaldehyde (Structural Formula 2-15 below) 24.4 g (0.20 mol),
[0256]
[0257] It was dissolved in 200.0 g of 2-ethoxyethanol. After adding 20.0 g of sulfuric acid while cooling in an ice bath, it was heated at 100°C for 3 hours and stirred to react. After the reaction, the obtained solution was reprecipitated with water, washed with water, filtered, and vacuum dried to obtain 65.0 g of a trifunctional hydroxy compound with a hydroxyl equivalent of 118 g / eq. The trifunctional hydroxy compound is R in formula (2-4): 1 ~R 4 All are methyl and R 5 and R 6 A compound containing hydrogen atoms.
[0258] Next, 59.0 g (0.17 mol) of the obtained trifunctional hydroxy compound, 400 g of methyl ethyl ketone, and 91.6 g (0.60 mol) of chloromethylstyrene (the following structural formula 2-16) were added to a 1000 ml four-necked flask.
[0259]
[0260] The temperature was raised to 60°C, and 33.7 g of potassium hydroxide dissolved in 101 g of methanol was added dropwise over 3 hours, and the reaction was further continued for 6 hours. After the reaction was completed, the mixture was filtered, the solvent was distilled off, and the mixture was reprecipitated with methanol, washed with a large amount of water, and dried under reduced pressure to obtain 102.4 g of vinyl resin (vinyl resin A). The basic structure of vinyl resin A is: 1 ~R 4 Both are methyl and R 5 and R 6It is hydrogen, has a vinyl equivalent of 225 g / eq, a hydroxyl equivalent of 12000 g / eq, a total chlorine content of 600 ppm, a melting point of 130°C, and an Mn of 780.
[0261] The GPC chart of the obtained vinyl resin A is shown in Figure 3 .
[0262] (Synthesis example 2-2)
[0263] In a 1000 ml four-necked flask, 65.3 g (0.35 mol) of 4,4'-dihydroxybiphenyl (the following structural formula 2-17) and
[0264]
[0265] 121.2 g of diethylene glycol dimethyl ether, 58.7 g (0.23 mol) of 4,4'-bis(chloromethyl)biphenyl (the following structural formula 2-18),
[0266]
[0267] Under a nitrogen stream, the temperature was raised to 170° C. while stirring, and the mixture was reacted for 3 hours, and further reacted with 7.8 g (0.04 mol) of dihydroxydiphenylmethane (4,4′-dihydroxydiphenylmethane (the following structural formula 2-19): 36.2%, 2,4′-dihydroxydiphenylmethane: 46.6%, 2,2′-dihydroxydiphenylmethane: 17.2%),
[0268]
[0269] A polyhydroxy resin of formula (2-7) (hydroxyl equivalent 129 g / eq) was produced.
[0270] After the reaction, 50.7 g of diethylene glycol dimethyl ether was recovered, 320 g of methyl ethyl ketone and 135.5 g of chloromethyl styrene were added, the temperature was raised to 60°C, 49.8 g of potassium hydroxide dissolved in 150 g of methanol was added dropwise over 3 hours, and the reaction was further carried out for 6 hours. After the reaction was completed, the mixture was filtered, the solvent was distilled off, reprecipitated with methanol, washed with a large amount of water, and dried under reduced pressure to obtain 141 g of a white solid vinyl resin (vinyl resin B) of formula (2-6) (i.e., formula (2-2)). The vinyl equivalent of vinyl resin B is 275 g / eq, the hydroxyl equivalent is 15000 g / eq, the total chlorine is 300 ppm, the Mn is 1330, and the melting point is 145°C. The basic structure of the polyhydroxy resin and vinyl resin B is that in formula (2-6) and (2-7), A is a -CH2- group, the ratio (molar ratio) of e / (e+f) is 0.93, e is 4.2, and f is 0.3.
[0271] The GPC chart of the obtained vinyl resin B is shown in Figure 4 .
[0272] (Synthesis example 2-3)
[0273] 74.5 g (0.4 mol) of 4,4'-dihydroxybiphenyl and 18.4 g (0.08 mol) of 1,5-dibromopentane (the following structural formula 2-20) were placed in a 2 L four-necked separable flask.
[0274]
[0275] After dissolving in 500 g of N-methyl-2-pyrrolidone, 41.5 g of potassium carbonate was added, and the mixture was heated to 120° C. under a nitrogen stream while stirring. Then, 20.6 g (0.12 mol) of 2,6-dichlorobenzonitrile (the following structural formula 2-21) was added.
[0276]
[0277] Raise the temperature to 145°C and react for 6 hours. After adding 28.2 g of acetic acid to the reaction solution for neutralization, distill off N-methyl-2-pyrrolidone under reduced pressure. After adding 250 mL of methyl isobutyl ketone to the reaction solution to dissolve the product, remove the generated salt by washing with water. Thereafter, remove the methyl isobutyl ketone by distillation under reduced pressure to obtain 72.6 g of hydroxy resin. The hydroxyl equivalent of the obtained hydroxy resin is 225 g / eq, and Mn is 520. The p value (average value) is 2.3. The basic structure of the hydroxy resin is a structural unit in which Y is a direct bond in formula (2-13), B has a benzonitrile structure, and -(CH2) q -(q=5) when both of these structural units.
[0278] Next, 74.3 g (0.33 mol) of the obtained hydroxy resin, 400 g of methyl ethyl ketone, and 61.0 g (0.40 mol) of chloromethylstyrene were added to a 1000 ml four-necked flask, and the temperature was raised to 60°C. 22.4 g (0.40 mol) of potassium hydroxide dissolved in 70 g of methanol was added dropwise over 3 hours, and the mixture was further reacted for 6 hours. After the reaction was completed, the mixture was filtered, the solvent was distilled off, reprecipitated with methanol, washed with a large amount of water, and dried under reduced pressure to obtain 84.3 g (vinyl resin C) of the formula (2-12) (i.e., formula (2-3)). The vinyl equivalent of the vinyl resin C was 341 g / eq, the hydroxy equivalent was 10000 g / eq, the total chlorine was 900 ppm, the Mn was 710, and the melting point was 174°C. The basic structure of vinyl resin C is as follows: in formula (2-12) and formula (2-3), q is 5, g is 1 to 3, h is 1 to 3, and p value (average value) is 1.8.
[0279] The GPC chart of the obtained vinyl resin C is shown in Figure 5, and the FD-MS spectrum is shown in Figure 6 .
[0280] (Synthesis example 2-4)
[0281] 40.8 g of 4,4'-bis(chloromethyl)biphenyl, 75.5 g of 4,4'-dihydroxybiphenyl and 120 g of diethylene glycol dimethyl ether were placed in a 1000 ml four-necked flask, and the mixture was heated to 160°C for 10 hours under a nitrogen stream while stirring. Then, the mixture was heated to 70°C, 280 g of diethylene glycol dimethyl ether and 129.5 g of chloromethylstyrene were added, and 100.0 g of 48% potassium hydroxide was added dropwise while the reaction was carried out. It was confirmed by gas chromatography that no chloromethylstyrene remained, and the solvent was recovered under reduced pressure. The obtained resin was dissolved in toluene, neutralized and washed with water to obtain a vinyl resin (vinyl resin D). The obtained vinyl resin D had a vinyl equivalent of 256 g / eq, a hydroxyl equivalent of 1500 g / eq, a total chlorine of 1270 ppm, an Mn of 1100, and a melting point of 210°C.
[0282] The higher melting point of vinyl resin D is speculated as follows. That is, since dihydroxydiphenylmethane was not used as a raw material, the content of biphenyl components was higher than that of Synthesis Example 2-2, or the melting point of the obtained hydroxy resin became higher because the biphenyl structure inhibited molecular motion. Therefore, it is speculated that since the solvent solubility of the hydroxy resin is relatively reduced, a large number of unreacted hydroxyl groups (polar groups with hydrogen bonding properties) remain in the subsequent reaction with chloromethylstyrene, and the vinyl benzyl ether group with flexibility is reduced.
[0283] (Synthesis example 2-5)
[0284] In a 1000 ml four-necked flask, 50.0 g of dihydroxydiphenylmethane (4,4'-dihydroxydiphenylmethane: 36.2%, 2,4'-dihydroxydiphenylmethane: 46.6%, 2,2'-dihydroxydiphenylmethane: 17.2%), 400 g of methyl ethyl ketone, and 80.1 g of chloromethylstyrene were added, and the temperature was raised to 60°C. 29.5 g of potassium hydroxide dissolved in 88 g of methanol was added dropwise over 3 hours, and the mixture was further reacted for 6 hours. After the reaction was completed, the mixture was filtered, the solvent was distilled off, and the mixture was reprecipitated with methanol, washed with a large amount of water, and dried under reduced pressure to obtain 95.4 g of a vinyl resin (vinyl resin E). The vinyl equivalent of the vinyl resin E was 217 g / eq, the hydroxyl equivalent was 17000 g / eq, the total chlorine was 400 ppm, the Mn was 440, and the melting point was 80°C.
[0285] The low melting point of the vinyl resin E is presumed to be due to the following reason: Unlike Synthesis Example 2-4, since only dihydroxydiphenylmethane was used as a raw material to react with chloromethylstyrene, the melting point of the obtained hydroxy resin was presumed to be lower than that of Synthesis Example 2-2 because no biphenyl component was contained.
[0286] Examples 2-1 to 2-5, Comparative Examples 2-1 to 2-4
[0287] Vinyl resins A to E obtained in Synthesis Examples 2-1 to 2-5 were used as vinyl resins, talc (additive A, average particle size 10 to 15 μm, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used as an additive, PERBUTYLP (manufactured by NOF Corporation) of an organic peroxide was used as a curing accelerator, ADK STAB AO-60 (manufactured by ADEKA Corporation) was used as an antioxidant, spherical alumina (DAW-10 manufactured by Denka, average particle size 12.2 μm) was used as an inorganic filler A, and spherical silica (FB-8S manufactured by Denka) was used as an inorganic filler B. They were mixed in the proportions shown in Table 1 and dissolved in a solvent to prepare a uniform composition. This composition was applied to a PET film and dried at 130° C. for 5 minutes to obtain a resin composition (resin sheet). The composition taken out from the PET film was sandwiched between mirror plates and cured while applying a pressure of 2 MPa at 130° C. for 15 minutes and at 210° C. for 80 minutes under reduced pressure. Table 2 shows the properties of the obtained cured product.
[0288] The cured products formed from the vinyl resin compositions of the Examples have higher thermal conductivity than those of the Comparative Examples and exhibit excellent physical properties such as a low dielectric constant and a low dielectric loss tangent.
[0289] [Table 2]
[0290]
[0291] [Effects of the Second Embodiment and Industrial Applicability]
[0292] The vinyl resin composition exemplified in the second embodiment has excellent solvent solubility and is suitable for vinyl resin compositions and cured products thereof used in applications such as lamination, molding, casting, and bonding. Furthermore, the cured product is also excellent in heat resistance, thermal decomposition stability, thermal conductivity, low dielectric constant, low dielectric loss tangent, and flame retardancy, and is therefore suitable for packaging of electrical and electronic components, circuit board materials, and the like.
[0293] The vinyl resin composition and cured product of the second embodiment of the present invention are useful as electronic materials for high-speed communication devices, and as materials that can easily dissipate heat generated by electronic parts or wiring and have little signal loss.
Claims
1. A resin composition, characterized in that A resin composition comprising at least a crystalline resin and an additive, wherein the additive is a layered clay mineral, and the layered clay mineral is contained in an amount of 1 to 20 parts by weight relative to 100 parts by weight of the resin component. The melting point of the crystalline resin is higher than 80° C. and lower than 200° C.
2. The resin composition according to claim 1, characterized in that The additive is talc or mica.
3. The resin composition according to claim 2, characterized in that The additive is talc.
4. The resin composition according to claim 1, characterized in that The crystalline resin is an epoxy resin and / or a vinyl resin.
5. The resin composition according to claim 4, characterized in that The crystalline resin is an epoxy resin having a melting point of more than 80°C and not more than 180°C and / or a vinyl resin having a melting point of 90 to 200°C.
6. The resin composition according to any one of claims 1 to 5, characterized in that The crystalline resin is an epoxy resin. The resin composition contains a curing agent. In measurement of a cured product of the resin composition by X-ray diffraction (XRD), a diffraction peak is detected in a region where a diffraction angle 2θ is 15° or more and less than 25°.
7. The resin composition according to claim 6, characterized in that The epoxy resin is represented by the following general formula (1-1) or (1-2), In formula (1-1), G represents a glycidyl group, A independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO- or a divalent hydrocarbon group having 1 to 6 carbon atoms, and n represents a number from 0 to 20. In formula (1-2), Y independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO-, -COO-, -CONH-, -CH2- or -C(CH3)2-, and B independently represents a benzonitrile structure or -(CH2) q -, p represents a number from 0 to 15, and q represents a number from 3 to 10.
8. The resin composition according to any one of claims 1 to 5, characterized in that The crystalline resin is a vinyl resin having a vinyl equivalent of 150 to 1000 g / eq, a hydroxyl equivalent of 5000 g / eq or more, and a total chlorine content of 2000 ppm or less.
9. The resin composition according to claim 8, characterized in that The vinyl resin is represented by any one or more of the following general formulas (2-1) to (2-3), In formula (2-1), R 1 ~R 6 each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms, In formula (2-2), A independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO- or a divalent hydrocarbon group having 1 to 6 carbon atoms, X independently represents a benzene ring, a naphthalene ring or a biphenyl ring, and n represents a number from 0 to 20. In formula (2-3), Y independently represents a single bond, an oxygen atom, a sulfur atom, -SO2-, -CO-, -COO-, -CONH-, -CH2- or -C(CH3)2-, and B independently represents a benzonitrile structure or -(CH2) q -, p represents a number from 0 to 15, and q represents a number from 3 to 10.
10. The resin composition according to any one of claims 1 to 5, characterized in that Contains 20 to 90 wt% of an inorganic filler other than layered clay minerals.
11. The resin composition according to any one of claims 1 to 5, characterized in that A resin composition that provides a cured product with high thermal conductivity.
12. The resin composition according to claim 6, characterized in that A resin composition providing a cured product having a crystallinity of 10% or more and having high thermal conductivity. 13 . A cured product obtained by curing the resin composition according to claim 1 .
Citation Information
Patent Citations
Liquid crystal epoxy monomer and liquid crystal epoxy resin
JP1997118673A
Epoxy resin composition for semiconductor sealing and semiconductor device
JP1999147936A
Insulation composition
JP1999323162A
Epoxy resin composition for sealing and semiconductor device
JP2002309067A
Wiring board
JP2009170493A